The algorithm of treatment of the patient with relapsing-remitting multiple sclerosis with suboptimal response:the example of a clinical case - Popova, E. V.; Bryukhov, V. V.; Boyko, A. N.; Krotenkova, M. V. (Medical Council, 2018)
This article presents a clinical case of suboptimal response to multiple sclerosis therapy and an algorithm for treatment, taking into account the existing performance criteria.